Estudo de altas pressões por espectroscopia Raman no cristal de Nitrato de L-Alanina - SOARES, Rilleands Alves (2017)
In this work nitrate L-Alanine crystals (LAN) were prepared by slow evaporation technique at room temperature and characterization by X-ray diffraction and Raman scattering at room temperature and high pressures in the amino acid salt crystals LAN. The crystals grew after six months of rest. The growth solution was acidic with pH 1.0. With the XRD pattern of the material and the Rietveld analysis, it was found that at room temperature LAN crystallizes in orthorhombic space group (P212121) with four molecules per unit cell. The refinement of the quality parameters were satisfactory, with Rp = 5.52%, 7.73% and S = 1.4. The results of Raman scattering with hydrostatic pressure variation between 0 GPa and 7.4 GPa, show that the LAN crystal undergoes a phase transition between 3.5 and 4.1 GPa, as suggested by the changes in the vibrational modes, both In the low wave number as in the internal mode regions. The correlation between the configuration of hydrogen bonding at ambient pressure and the occurrence of phase transition with pressure variation was proposed. After decompression at ambient pressure, the original spectra were recovered indicating that the phase transitions are reversible.